Recreational and tourist potential of the transnistrian district of Ukraine - Kilinska, K.; Yavorska, V.; Kostashchuk, V.; Smyk, O. (Journal of Education, Health and Sport, 2021)
The article proves that the sphere of tourism, in contrast to other sectors of the economy, makes it possible to implement the concept of self-development, self-government and self-financing from its own resources, own financial sources. The article emphasizes that a special place in the development of tourism in Transnistria in the future should belong to the Dniester Reservoir. In fact, this determines the relevance and practical significance of this study. The tourist and recreational complex of Transnistria is a leading factor in the development of the region’s economy. The article reveals the peculiarities of the development of recreational and tourist conditions and resources of the Transnistrian district of Chernivtsi region.